Imaging Findings in Dogs and Cats With Presumptive Sclerosing Encapsulating Peritonitis - Gremillet, Bérengère C. H.; Porsmoguer, Charles; Bolen, Géraldine; Billen, Frédéric; Noël, Stéphanie; Brutinel, Flore; Busoni, Valeria (Frontiers in Veterinary Science, 2022)
This retrospective case series describes imaging findings in seven dogs and two cats with a presumptive diagnosis of sclerosing encapsulating peritonitis (SEP) between 2014 and 2021. Peritoneal effusion was present in all animal patients. Sonographically, echogenic fluid with or without echogenic intraperitoneal septations, gathered or corrugated bowel loops, and abdominal lymphadenomegaly were suggesting an inflammatory process and the presence of adhesions. Gathering of the bowel with abdominal distension and/or signs of intestinal obstruction were major findings on radiographs. Abdominal fat stranding was an additional finding in animals undergoing a CT examination. Previous surgery, pregnancy, and the presence of a perforating foreign body were potential predisposing causes in 4/9 animals. Peritonitis was septic in 4/9 animals. As SEP is a rare condition but life threatening, this detailed description of imaging findings in a short case series can be useful for a presumptive diagnosis and surgical planning.